LONG TERM QUALITY OF LIFE HEALTH OUTCOMES IN PATIENTS RECEIVING ULTRASOUND GUIDED INJECTIONS: PRELIMINARY ANALYSIS. Issue 4 (28th April 2020) - Stracciolini, Andrea; Kobelski, Greggory; McKee-Proctor, Maxwell; Yen, Yi-Meng; d'Hemecourt, Pierre; Sugimoto, Dai
BACKGROUND: Hip pain is a common complaint in athletes of all ages. Hip pathology includes both intra- and peri-articular pain generators. Ultrasound (US) evaluation and guided injections are used in the clinical setting for diagnostic and therapeutic purposes. However, evidence regarding the impact of US-guided injections on quality of life (QoL) health outcomes in patients with hip pain and injury is understudied. PURPOSE: To examine the long-term efficacy of US-guided injections on QoL outcomes in patients presenting to a tertiary level academic hip preservation program. METHODS: Prospective longitudinal study design was used to evaluate 12-55 years old patients with hip pain/pathology. Patients completed a Hip Disability and Osteoarthritis Outcome Score (HOOS) questionnaire at the initial evaluation, 1.5-months, 4.5-months, and 12-months. Main outcome measures included change in QoL HOOS scores. Repeated measures analysis of variance (ANOVA) was performed to compare patients who received US-guided injections and patients who did not receive US-guided injections over time. Bonferroni pairwise comparison was performed as a post-hoc analysis. RESULTS: A total of 175 patients were included with a mean age of 24.1±9.8 years. There were 104 patients who received US-guided injections while 71 patients did not have US-guided injections. An interaction between US-guided injections over 12-months on QoL scores was identified. QoL increase over time was 6.5 points in patients without US-guided injection compared to 10.0 points in patients who had an US-guided injection ( P =0.040, Figure 1). Main effect of US-guided injections on QoL was not detected ( P =0.276). However, main effect of time on QoL was found ( P =0.003). Bonferroni post-hoc analysis indicated differences between initial evaluation and 1.5 months ( P =0.004, Figure 2), and initial evaluation and 12-months ( P =0.002, Figure 3). CONCLUSION: US-guided injections appeared to improve quality of life outcomes over the 12-month study period. US-guided injections may serve to help patients with hip pain presenting to clinic over time and promote and support non-surgical treatment regimes. : Figure 1. Interaction Effect of US-guided Injection during a 12-months (P=0.040) Figure 2. Main Effect of Time US-guided Injection between Initial Visit and 1.5 Months Figure 3. Main Effect of Time US-guided Injection between Initial Visit and 12 Months